Extracellular vesicles secreted by human cardiosphere-derived cells attenuate electrophysiological remodelling in an in vitro model of atrial fibrillation. (14th October 2021) - Gomez-Cid, L; Moro-Lopez, M; De La Nava, A S; Fernandez, A I; Fernandez-Santos, M E; Atienza, F; Grigorian, L; Fernandez-Aviles, F
Abstract: Background: Stem cells and their secreted extracellular vesicles (EVs) have shown different cardioprotective effects. However, their impact on the electrophysiological properties of the heart tissue remains controversial. While the use of some progenitor cells seems to have antiarrhythmic potential, the use of cardiomyocyte-like cells may be proarrhythmic. The mechanisms behind, and whether these effects are linked to cell engraftment and not to their secreted products is not fully known. Purpose: The aim of this study was to investigate the electrophysiological modifications induced by extracellular vesicles secreted by human cardiosphere-derived cells (CDC-EVs) in an in vitro model of atrial fibrillation in order to explore their potential antiarrhythmic effect. Methods: CDCs were derived from cardiac biopsies of patients who underwent cardiac surgery for other reasons. Purified CDC-EVs resuspended in serum-free media (SFM) vs. SFM alone were added to HL-1 atrial myocyte monolayers presenting spontaneous fibrillatory activity. After 48 hours, the monolayers were fully confluent, and the electrophysiological properties were analysed through optical mapping in both the treated (n=9) and control plates (n=9). Optical mapping recordings of the monolayers were analysed with Matlab for the activation frequency, activation complexity, rotor dynamics (curvature and meandering) and conduction velocity. Results: CDC-EVs reduced activation complexity of the fibrillating atrial monolayers by ∼40% (2.74±0.59 vs. 1.61±0.16 PS/cm 2, p<0.01). This reduction in activation complexity was accompanied by larger rotor meandering (1.47±0.82 vs. 4.32±2.25 cm/s, p<0.01) and decreased curvature (1.79±0.40 vs. 0.87±0.24 rad/cm, p<0.01) in the treated group. Despite reduction in the activation complexity, activation frequency did not change significantly between both groups. This could be in part because CDC-EVs increased conduction velocity by 80% (1.32±0.57 vs. 2.65±0.87 cm/s, p<0.01). Low conduction velocity has been linked to higher reentry recurrence, and lower meandering and higher curvature to higher rotor stability and harder AF termination. Therefore, CDC-EVs seem to drive cardiomyocytes to a less arrhythmic profile reducing activation complexity and preventing remodelling by increasing conduction velocity and modifying rotor dynamics. Conclusions: CDC-EVs significantly modify conduction velocity and rotor dynamics, therefore reducing fibrillation complexity and remodelling to drive atrial myocytes to a less arrhythmogenic profile. Testing CDC-EVs in more robust models of atrial fibrillation, the most common sustained arrhythmia in humans with significant morbidity and mortality, is of special interest. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Instituto de Salud Carlos III, Ministerio de Ciencia e Innovaciόn, CIBERCV, Spain